Translational informatics in smart healthcare - Shen, Bairong (Singapore : Springer, 2017)
"This book is about the transformation of the biomedical information to smart healthcare, the chapters are designed to discuss the health associated factors such as genetics, lifestyle, nutrition and environmental factors. The interactions of these factors and the informatics for the analyses of their effects on health are also covered. The era of aging is approaching and the P4 (predictive, preventive, personalized and participatory) medicine paradigm is becoming practical and reality. According to the Kondratiev's long wave theory, IT (information technology) and health will be the next technological revolution for the new economic cycle. This book is written for biomedical informatics scientists, clinicians, health practitioners and researchers, etc."--Publisher's description.
Informatics for precision medicine and healthcare / Jiajia Chen, Yuxin Lin, Bairong Shen -- Genetic test, risk prediction, and counseling / Maggie Haitian Wang, Haoyi Weng -- Newborn screening in the era of precision medicine / Lan Yang, Jiajia Chen, Bairong Shen -- Trace elements and healthcare: a bioinformatics perspective / Yan Zhang -- Tongue image analysis and its mobile app development for health diagnosis / Ratchadaporn Kanawong, Tayo Obafemi-Ajayi, Dahai Liu, Meng Zhang, Dong Xu, Ye Duan -- Physical exercise prescription in metabolic chronic disease / Laura Stefani, Giorgio Galanti -- Informatics for nutritional genetics and genomics / Yuan Gao, Jiajia Chen -- Interactions between genetics, lifestyle, and environmental factors for healthcare / Yuxin Lin, Jiajia Chen, Bairong Shen -- Cohort research in mics and preventive medicine / Yi Shen, Sheng Zhang, Jie Zhou, Jiajia Chen.
Includes bibliographical references.
PHR
Trim education
Keywords: Medical informatics; Translational Medical Research; Pharmacy